Efisiensi Teknis, Alokatif dan Ekonomis pada Usahatani Padi Organik di Kecamatan Cipatujah - Arifin, Muhamad Ilham Gumilang; Djuliansah, Dedi; Nuryati, Rina (Universitas Galuh, 2025)
The UPLAND program aims to meet food needs by increasing productivity and farmer income. As part of the program, farmers are required to adopt certified organic rice cultivation practices. To successfully manage their farming activities farmers must use production input efficiently to achieve optimal yields and improve income from organic rice farming. This study aims to analyze the efficiency of input use in organic rice farming in terms of technical, allocative, and economic efficiency. The research was conducted in Cipatujah Subdistrict, the location of the UPLAND Program implementation, from July to November 2024. A survey method was used with questionnaires and interviews as instruments. The sampling technique employed was simple random sampling, with 106 farmer respondents. The data were analyzed using the Stochastic Frontier production function. The results showed that the average organic rice farmers in the region have achieved technical efficiency. However, allocative and economic efficiency have not yet been achieved, indicating the need for further optimization in the allocation and combination of production factors.